2009
DOI: 10.1097/gme.0b013e3181847619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anthocyanins on learning and memory of ovariectomized rats

Abstract: Our results suggest that anthocyanins improve learning and memory of rats with estrogen deficit caused by ovariectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Recent studies have shown that phytoestrogens (Ewies, 2002) can alleviate the symptoms of estrogen deficit after menopause (Shi et al, 2008;Varadinova et al, 2009) and have neuroprotective effects in toxin-induced neurodegenerative models (Shi et al, 2007). DJS contains phytochemicals with estrogen-like activities and neuroprotective effects, including paeoniflorin from Paeoniae Radix and ligustilide from Cnidium Rhizoma and Angelicae Gigantis Radix, and ferulic acid from Angelicae Gigantis Radix.…”
Section: Resultsmentioning
confidence: 98%
“…Recent studies have shown that phytoestrogens (Ewies, 2002) can alleviate the symptoms of estrogen deficit after menopause (Shi et al, 2008;Varadinova et al, 2009) and have neuroprotective effects in toxin-induced neurodegenerative models (Shi et al, 2007). DJS contains phytochemicals with estrogen-like activities and neuroprotective effects, including paeoniflorin from Paeoniae Radix and ligustilide from Cnidium Rhizoma and Angelicae Gigantis Radix, and ferulic acid from Angelicae Gigantis Radix.…”
Section: Resultsmentioning
confidence: 98%
“…They have also been reported to have antioxidant activity in vitro, inhibiting the oxidation of human low density lipoprotein (LDL) (Astadi et al, 2009). Anthocyanins from various sources including mulberry fruit display neuroprotective and brain benefiting properties (Kang et al, 2006;Varadinova et al, 2009;Zafra-Stone et al, 2007). The presence of anthocyanins in soybeans was first reported by Nagai (1921), and subsequently several groups (Yoshida et al, 1996) have identified different anthocyanins in different black soybean varieties.…”
Section: Discussionmentioning
confidence: 95%
“…Anthocyanins from various sources including mulberry fruit have been reported for their neuroprotective and brain health benefits (Kang et al, 2006;Zafra-Stone et al, 2007;Varadinova et al, 2009;Chen and Luo, 2010). Although black soybeans have been consumed as medicinal food in Korea, China and Japan for hundreds of years (Xu and Chang, 2008), their health benefits and underlying mechanisms have not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…The rats were treated by gavage with ANT (30 and 100 mg/kg body weight) during this period (approximately 10 a.m.). The dose of ANT was chosen on the basis of protocols developed by our group (data not published) and previous studies that indicated neuroprotection [29,[49][50][51]. The control groups received only vehicle (2-ml/kg daily gavage of saline for 7 days).…”
Section: Treatmentmentioning
confidence: 99%